Litterfall, nutrients and fishery production in Kuala Sibuti mangrove, Malaysia - Hoque, Mohammed Muzammel (2015)
Research on ecological productivity of pristine mangroves in Sarawak is scanty. This study was carried out to determine some of the important attributes of ecological productivity, especiallly litterfall, nutrients release through decomposition, sediment productivity, nutrient inputs from different sources, fisheries diversity and production of undisturbed Kuala Sibuti mangrove, Sarawak, Malaysia from January 2013 to March 2014. Three sampling plots, each 100 m × 100 m (river mouth, middle and last part of the forest) were established considering the structure, density and topography of the mangrove to represent the whole forest for collection of data and information related to this study. Annually 1640.82 g/m2 dry weight of litterfall was estimated, of which Rhizophora apiculata contributed 92.94%, followed by Xylocarpus granatum (4.01%) and other species (3.05%). Total litterfall of both the species did not vary seasonally and the litterfall production of this forest was higher compared to other R. apiculata dominated tropical mangroves of the world. Monthly total litter standing crop correlated negatively (r=-0.58, p<0.05) with number of high tide that flooded, suggesting that tidal frequency determines the amount of litter remains on the forest floor. The decay constants (k) of almost all the litter components of the two species varied among the components and between the species. The half-life (T50%) and 95% lifespan (T95%) of non-leafy components such as flower, propagule, stipule and twig of both the species were remarkably high compared to the leaf. The slow decay rates of maximum litter components of the species positively correlated with the higher content of lignin, suggesting significant influence of lignin on the rate of litter decomposition. The order of nutrients release from the various litter components of the species was leaf > flower > propagule > stipule > twig. The annual rate of tidal sediment accumulation in the mangrove was 0.93 g/cm2. The monthly accumulation of sediments correlated positively (r=0.69) with the rate of monthly rainfall. The tidal sediments were relatively rich in texture, organic matter, organic carbon, cation exchange capacity and nutrients. The nutrient contents were also higher in the tidal borne sediments compared to the surface (0-5 cm) and deeper (30-50 cm) soils of the study area. In general, highly significant positive correlation between the sediment nutrients and corresponding nutrient contents in the components (leaf, stipule, flower, propagule, stem, bark and root) of R. apiculata and X. granatum trees, saplings and seedlings indicates the nutritive roles of tidal borne sediments in the productivity of this mangrove ecosystem. Nutrients of surface soil, especially C, N, P, K, Na and S correlated positively with the nutrients of deeper soil. Pore and river water nutrients (NH4 +, NO3 -, PO4 =, K, Ca, Mg and Na) of this forest were higher in the dry season and NH4 +, Ca, Mg and Na of pore water correlated positively with the nutrients of river water. Although the overall nutrient contents were higher in the surface soil, most of the nutrients, especially P, S, Mg and Na of deeper soil correlated positively with the corresponding nutrient contents of plant components of the two species, suggesting the plants uptake more nutrients from the root zone of the deeper soil. The lower C/N ratio is related to higher nutrition. Relatively lower C/N ratio was found in all the components of R. apiculata trees (47- 104), saplings (42-81) and seedlings (41-60) than that of X. granatum trees (47-146), saplings (44-95) and seedlings (30-60) components. This suggests that the dominant species R. apiculata plays the important roles in the nutrient dynamics of Kuala Sibuti mangrove forest. Kuala Sibuti mangrove estuary is relatively species rich in terms of fishery production and diversity, comprising 60 species from 32 families. Among all the species, Coilia dussumieri was the most dominant species (22.63%) followed by Nemapteryx caelata (11.85%), Otolithes ruber (7.85%) and Ilisha elongata (5.80%). The diverse species composition of fishery resources in this estuary could be due to favorable hydrobiological factors as well as enormous detritus and nutrients supplied from the mangrove forest. The findings of this study acknowledge that ecologically Kuala Sibuti mangrove is a highly productive ecosystem. The dominant species R. apiculata plays the key roles behind its productivity. The outcomes of this study would be useful for the scientific community to conduct further in depth research in various dimensions as well as to realize the importance of pristine mangrove forests.